Spinal cord stimulation for refractory pericarditis: a case report and a review of the mechanism of action - Elsliger, Simon; Saucier, Jacob; Schneider, Andre; El Helou, Antonios (Frontiers in Pain Research, 2023)
In recent years, spinal cord stimulation (SCS) has emerged as a promising management option for chronic pain of multiple aetiologies. While its effectiveness has been strongly suggested in many patients, SCS' exact mechanism of action is incompletely understood. This article reviews leading mechanisms underlying SCS' analgesic and cardiovascular effects, in addition to reporting SCS' novel benefits in a case of recurrent pericarditis.Historically, the analgesic properties of SCS were thought to arise via stimulation of the spinothalamic tract. Although this mechanism has been thoroughly detailed, new research and patient outcomes from SCS have revealed numerous additional properties of SCS that are seldom explained by this mechanism. Evidence suggests that SCS enhances CGRP release, modulates inflammatory cytokines secretion, sympathetic tone, and inhibitory neurotransmitter secretion.These distinct mechanisms likely collectively contribute to SCS' therapeutic effects on the cardiovascular system and pain management.